Bear attacks on people in Slovakia in 2000 - 2016 - Haring, Michal (University of South-Eastern Norway, 2018)
Human-wildlife conflicts worldwide involve both herbivore and carnivore species. Conflicts often result in negative consequences on both sides. Large carnivores, including bear species, are often involved. Brown bears (Ursus arctos) usually avoid interactions with humans, but on rare occasions may attack during encounters. There are about 1000 – 1500 brown bears in Slovakia with a female-biased sex ratio. Only direct contacts or injuries caused by brown bears were considered as attacks. During the period 2000 – 2016, bears caused human injuries (but no fatalities) in 54 recorded incidents. The highest number of attacks occurred in 2014 (8) and 2007 (7). Attacks peaked in June and occurred significantly more often during weekends than on weekdays. Hunting and gathering were activities most related to brown bear attacks in Slovakia while unaccompanied people were more exposed to attacks than those in groups. Females bears carried out significantly more attacks (20 of 24) compared to male bears where sex of the bear was confirmed. Habituated or food-conditioned bears were involved in 11% (6/54) attacks on people. On average, victims first time spotted bears from approximately 12 m and those who initially stayed still spent less time in hospital than people who tried to run away. Dense vegetation along with low visibility of surroundings were two common risk factors. The presence of a dog usually aggravated situations while carrying a gun did not guarantee safety. None of the victims was carrying bear spray, which is an effective bear deterrent. Raising awareness of the general public and particular interest groups most often present in bear country could be key for better understanding between the two species: human and bear. publishedVersion